Lipoprotein transport and metabolism markers in patients with myocardial infarction in the Biobank of Yugra blood sample collection - A. S. Vorobyov; M. Yu. Donnikov; O. S. Glotov; L. V. Kovalenko; K. Yu. Nikolaev; I. A. Urvantseva; Yu. A. Drenina; A. V. Morozkina; G. N. Chernysheva (Кардиоваскулярная терапия и профилактика, 2025)
Aim. To evaluate clinical associations and predictive value of lipoprotein transport and metabolism markers determined in a collection of serum samples from patients with myocardial infarction (MI).Material and methods. Collection of blood samples from 88 patients with the acute MI was created in the Biobank of Yugra laboratory for subsequent biochemical assessment of serum levels of lipoprotein transport and metabolism markers. All patients were included in a clinical prospective study for 48 months with registration of medical events and remote tomographic assessment of coronary artery (CA) involvement upon follow-up completion.Results. Direct associations were established between proprotein convertase subtilisin/kexin type 9 (PCSK9) levels and low-density lipoprotein cholesterol levels, coronary atherosclerosis, Global Registry of Acute Coronary Events (GRACE) 2.0 risk score, and the risk of recurrent acute coronary syndrome. Lipoprotein (a) levels >50 mg/dl were detected in 28,4% of patients with MI and were associated with prior medical events, coronary and non-coronary artery atherosclerosis, comorbidity, recurrent coronary lesions, and the risk of major cardiac events at the end of follow-up. A relationship was established between a high (5,14) triglyceride-glucose index and comorbidity, recurrent coronary lesions, and the death risk at the end of follow-up.Conclusion. The Biobank of Yugra laboratory is an effective base for laboratory research. Lipoprotein transport and metabolism markers are associated with clinical factors, comorbidity, vascular atherosclerosis and a negative prognosis in patients with MI.